Navigating Ethical Marketing: How Transparency Influences Brand Loyalty in the Digital Age - Hakiki, Ridwan; Henryanto Abaharis, Nurlina Nurlina, (Pascasarjana STIE Amkop Makassar, 2024)
This study explores the role of transparency in digital marketing and its impact on consumer trust and brand loyalty in the digital age. As consumers become more informed and discerning, they increasingly expect brands to be open about their business practices, product information, and ethical standards. The research examines how transparent marketing strategies foster consumer trust and enhance long-term loyalty. It also investigates the broader implications of ethical marketing in the digital landscape. Through qualitative methods, including in-depth interviews, document analysis, and case studies, the findings reveal that transparency plays a pivotal role in building trust and cultivating loyalty among consumers. Additionally, the study highlights the growing importance of ethical marketing practices as businesses adapt to an increasingly digital and interconnected world. The results suggest that businesses prioritizing transparency and ethical communication are more likely to retain loyal customers and enhance their market reputation. This study provides valuable insights for marketers seeking to implement effective digital strategies that align with consumer expectations and build sustainable relationships. Keywords: Digital marketing, Transparency, Consumer trust, Brand loyalty